Inhaled salbutamol intoxication - Cristina Elena Singer; Carmen Simona Cosoveanu; Jaqueline Abdul-Razzak; Alina Mandache; Maria Madalina Singer; Mihaela Popescu; Alin Iulian-Silviu Popescu; Cristina Geormaneanu (Amaltea Medical Publishing House, 2023)
In the specialized literature, there are few cases of inhaled salbutamol intoxication, being the most used bronchodilator in children's asthma. We describe the situation of a 15-year-old teenager who inhaled salbutamol, in the context of an asthma attack, with each episode of coughing. At admission, the patient was conscious with a serious general state, afebrile, conscious, psychomotor agitation, tachycardic (heart rate=140/bpm), precordial pain, polypnea, dyspnea, with respiratory effort, hemodynamically stable, blood pressure=130/77 mmHg. Investigations showed hyperglycemia and hypokalemia. After the treatment, the evolution was favorable.